2013
DOI: 10.1158/1940-6207.capr-13-0113
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Adenoma Stem-like Cell Populations: Associations with Adenoma Characteristics and Metachronous Colorectal Neoplasia

Abstract: Cancer stem cells have tumor-initiation and tumor-maintenance capabilities. Stem-like cells are present in colorectal adenomas, but their relationship to adenoma pathology and patient characteristics, including metachronous development of an additional adenoma (“recurrence”), have not been studied extensively. We evaluated the expression of aldehyde dehydrogenase isoform 1A1 (ALDH1A1), a putative stem cell marker, in baseline adenomas from the placebo arm of chemoprevention trial participants with colonoscopic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…We have also found that grading scores of LGR5 and ALDH1 positive cells in the cancerous epithelium were significantly increased in CRC patients with advanced TNM stages than those with early stages. Those observations are consist with other groups’ findings [ 15 , 26 32 ], and imply that increased stem-like cell density might be the potential predicators for disease stage progression in both the adenoma and CRC. Mesenchymal stem like cell can be observed in the tumor stroma, it plays a critical role in remodeling tumor stroma and forming a supportive environment for cancer growth and metastasis [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We have also found that grading scores of LGR5 and ALDH1 positive cells in the cancerous epithelium were significantly increased in CRC patients with advanced TNM stages than those with early stages. Those observations are consist with other groups’ findings [ 15 , 26 32 ], and imply that increased stem-like cell density might be the potential predicators for disease stage progression in both the adenoma and CRC. Mesenchymal stem like cell can be observed in the tumor stroma, it plays a critical role in remodeling tumor stroma and forming a supportive environment for cancer growth and metastasis [ 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Several potential stem-like markers have been used to identify stem cells in adenomas/CRC. LGR5 and ALDH1 are the two most promising and established stem-like markers and have been frequently used [ 3 , 5 , 7 , 10 , 15 ]. Studies have reported that LGR5 and ALDH1 expression can reflect the changes in stem-like cells during the process of colorectal tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, colon cancer stem cells secrete high levels of ALDH1A1 that cause extracellular detoxification of maphosphamide [23] and ALDH1A1 also confers resistance of COLO 205 cells to cyclophosphamide [42]. Consistently, ALDH1A1 expression in colorectal adenoma is associated with a higher risk of metachronous adenoma independent of adenoma size or histopathology [43]. CRC patients with circulating tumor cells expressing ALDH1, survivin and MRP5 have shorter PFS [44], and ALDH1A1 rs1342024 polymorphism associates with shorter time to tumor recurrence [26].…”
Section: Discussionmentioning
confidence: 99%
“…Building on this and more recent work in the molecular study of premalignancy (4,5), CaPR senior editor Ignacio Wistuba is heading a new minireview series focused on the early pathogenesis of selected human tumors.…”
Section: Greetings Colleaguesmentioning
confidence: 99%